1961
DOI: 10.1149/1.2428062
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Functions and Parameters in the Theory of Hydrogen Overpotential

Abstract: It is shown that the current density‐overpotential relationship for several mechanisms of the hydrogen evolution reaction can be expressed conveniently in terms of one or the other of two characteristic functions: g1=}{exp][)( α−12 η normalsinh )( 12η  /i,g2= tanh 12η /i½. The following parameters are convenient: a, the transfer coefficient for the oxidation reaction; θ0 , the fraction of the surface covered by H atoms at equilibrium, io=false(normaldi/dη)η=0 ; and ρ=false{d normalIn false[θ/false(1−θfalse)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1961
1961
1998
1998

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…is found to be 7.25 x 10 -3 A/cm 2. Equation [13] is similar to the one derived by Castellan (10). Schuldiner (8) has shown that for 0.05 to 0.7V, im is independent of potential.…”
Section: H2 Dissociation 41mentioning
confidence: 69%
“…is found to be 7.25 x 10 -3 A/cm 2. Equation [13] is similar to the one derived by Castellan (10). Schuldiner (8) has shown that for 0.05 to 0.7V, im is independent of potential.…”
Section: H2 Dissociation 41mentioning
confidence: 69%
“…Using these definitions, the steady-state conditions are written in detail and in their functionality. i--j = ]2(01, Cl) [9] i --j = f3 (cl) [10] j = f4(01, ul) [11] j = I5(ltl, u2) [ …”
Section: The Steady-state Conditionsmentioning
confidence: 99%
“…Considering only the functionality we conclude from Eq. [8], [9], and [10] that s can be expressed as a function of i and i-j only. Successive elimination of c2, 82, u2, Ul, cl, and 81 from Eq.…”
Section: Solution Of the Equationsmentioning
confidence: 99%
See 2 more Smart Citations